ANALISIS PENGARUH UKURAN PERUSAHAAN, AUDIT TENURE DAN PROFITABILITAS TERHADAP AUDIT DELAY - Sonya, Juwita; Maharani, Yunita; Tri Setyo Mulyani, Hendarti (Jurnal Akuntansi Bisnis Dan Keuangan, 2024)
The purpose of this research is to determine the influence of company size, audit tenure, and profitability on audit delay in property and real estate companies listed on the Indonesia Stock Exchange in the period 2020-2023. This study employs a quantitative descriptive approach using secondary data derived from the financial statements of companies and annual reports accompanied by independent auditor reports issued by the Indonesia Stock Exchange. The sampling technique used is purposive sampling with a total of 10 companies as samples. The analysis method employed is descriptive statistical analysis with hypothesis testing using multiple linear regression processed using SPSS 16.0.The research results show that company size has a partial effect on audit delay, Audit Tenure has a partial effect on audit delay, Profitability has no partial effect on audit delay. Company Size, Audit Tenure, and Profitability simultaneously influence audit delay in property and real estate companies listed on the Indonesia Stock Exchange for the 2020-2023 period.